MAIN FACTORS OF SOCIAL TOLERANCE AND SCIENTIFIC APPROACH - Nodira Julanovna Kunisheva (Bright Mind Publishing, 2025)
This article discusses the main factors and scientific approach to social tolerance.
Keywords: “Social tolerance”, globalization, empathy, social and cultural initiatives, discrimination, integration.